Influence Of Internal Communication To Productivity Of Work Employees at Le Meridien Bali Jimbaran Hotel - Pramana, I Ketut Andry; Sari, I Putu Ratna; Rahyuda, Irma (Jurnal Kepariwisataan dan Hospitalitas; Vol 2 No 3 (2018): Vol.2,No.3,2018DO - 10.24843/JKH.2018.v02.i03.p08, 2019)
Thi research is located in  Le Meridien Bali Jimbaran Hotel which is based on the existence of  miscommunication that occurs among employees that can hinder work productivity of employees of  Le Meriden Bali Jimbaran Hotel. The purpose of this research is to know the application of internal communication and to know the influence of internal communication to productivity of work employees in Jimbaran Bali Le Meridien Hotel. This research uses techniques of data collection through the methods of observation, interview, questionnaire, the study of librarianship, and documentation. A questionnaire distributed to 85 respondents which is an employee at the Hotel Le Meridien Bali Jimbaran. The measurement scale used is the likert scale and the analysis of its data using inferential statistic that validity test, reliability test, correlation analysis, simple linear regression analysis, determination analysis and t test. Implementation of internal communication are shown through daily operational activities that require interdepartmental coordination as well as employees that involves employees of the highest level, equivalent  , and lowest for providing services excellent with through media like whatsapp, handy talky, email, notice board as well as face-to-face.The results showed the existence of a positive influence of internal communication to productivity of work of employees. 38% employee productivity can be explained by the variable indicators of internal communication while the rest amounted to 62% is affected by other factors.. Advice that can be given to the Hotel Le Meridien Bali Jimbaran i.e. two-way communication emphasis, always open in taking decisions for employees and the management primarily superiors in order to keep his behavior since becoming a guide for employees the lower level.